Inguinal hernia in a female with broad ligament cyst as content - Chinnappan, Arul K.; Swaminathan, Shanthi P.; Kawarat, Vikas; Mani, Rajeswari; Anandakannan, Indrajit; Lalithkumar, Anusha; R., Kannan (International Surgery Journal, 2021)
Inguinal hernia in females is relatively uncommon as compared to males. It is interesting to note that 1 male in 5 and 1 female in 50 will eventually develop an inguinal hernia in a lifetime. The hernia sac may contain unusual structures such as the vermiform appendix, acute appendicitis, ovary, fallopian tube and, urinary bladder. Here we present a case of 20-year-old female presented with complaints of swelling in the right inguinal region. Diagnosed as a case of right inguinal hernia with Broad ligament cyst as content. Managed by laparoscopic excision of cyst and then right Lichtenstein repair for inguinal hernia.